2010
DOI: 10.1002/jcb.22735
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant vascular basement membrane derived multifunctional peptide blocks endothelial cell angiogenesis and neovascularization

Abstract: Angiogenesis is an innovative target in the therapy of cancer and other diseases, but the effects of anti-angiogenic drugs have been rather modest in clinical trials. We have developed a small peptide, recombinant vascular basement membrane derived multifunctional peptide (rVBMDMP), which significantly inhibits endothelial cells in vitro. Here we test the mechanisms of rVBMDMP in angiogenesis balance in assays of tubule formation, colony formation, and apoptosis in HUVE-12 endothelial cells. We also analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…However, the underlying detailed mechanism is not clear. Our previous study confirmed that rVBMDMP also binds integrin αVβ3 (4).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the underlying detailed mechanism is not clear. Our previous study confirmed that rVBMDMP also binds integrin αVβ3 (4).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, rVBMDMP selectively inhibited endothelial cell and human colon cancer cell proliferation, induced endothelial cell apoptosis in vitro and suppressed human colon cancer xenograft growth in Balb/c-nu mice (3). We determined that the interaction of rVBMDMP with αVβ3 integrin is critical for rVBMDMP binding to cells and mediates the rVBMDMP-induced inhibition of proliferation (4).…”
Section: Introductionmentioning
confidence: 99%
“…Tests were done in triplicate, counting a minimum of 200 total cells each. In addition, apoptotic cells were also analyzed using fluorescence-activated cell sorting (FACS) after staining with annexin V-fluorescein isothiocyanate [23] for determination of phosphatidylserine translocation. Viable cells were negative for both PI and Annexin-V; apoptotic cells were positive for Annexin-V and negative for PI, whereas late apoptotic dead cells displayed both high Annexin-V and PI labeling.…”
Section: Quantitation Of Apoptotic Cellsmentioning
confidence: 99%
“…Once obtained and expanded, immunocytochemical characterization of HUVE‐12 showed positive expression of CD 31 and Flk‐ 1 (current study). This cell line has also been shown by other laboratories to demonstrate angiogenic behaviour such as tube formation (Wang et al ., ). HUVE‐12 cells were split at a density of 1:4. hMSCs (Tulane Center for Gene Therapy; New Orleans, LA, USA) were cultured in αMEM cell culture medium that included Minimum Essential Media (GIBCO®) supplemented with 15% FBS, 1% antibiotic and 2 mM glutamine (GIBCO®).…”
Section: Methodsmentioning
confidence: 97%